Rehabilitation interventions in Rett syndrome: a scoping review. (30th May 2020) - Lim, Jan; Greenspoon, Dayna; Hunt, Anne; McAdam, Laura
Abstract : Aim: To summarize existing interventions and their outcomes in Rett syndrome (RTT) rehabilitation and identify gaps in the literature. Method: Five databases (Ovid MEDLINE, Ovid Embase Classic, Ovid PsycINFO, EBSCO CINAHL Plus, and ProQuest ERIC) were systematically searched up to 23rd July 2018 for studies describing rehabilitation interventions. Data on study participants, design, and outcomes were extracted. Results: Sixty‐two articles were included in the final review. Evidence consistently demonstrated that females with RTT can improve their gross motor, fine motor, and communicative skills with rehabilitation. All 11 interventions targeting gross motor function, namely ambulation, achieved functional improvements. Twenty of 24 articles describing fine motor rehabilitation studies succeeded in decreasing stereotypies, improving functional hand use, and/or reducing self‐injurious behaviors. Twenty‐one of 22 studies describing communication interventions succeeded in training choice‐making, communicative language, or socialization behavior. Other key findings include the positive interplay between physical and communicative rehabilitation outcomes, and the ability of females with RTT to improve their cognitive abilities during intervention. Interpretation: Rehabilitation can impact the daily lives of females with RTT and their caregivers in clinically meaningful ways. What this paper adds: Females with Rett syndrome (RTT) can make developmental gains across their life span. Long‐term intervention can improve the physical abilities of individuals with RTT. Low‐, medium‐, and high‐technology interventions can improve the communicative abilities of individuals with RTT. What this paper adds: Females with Rett syndrome (RTT) can make developmental gains across their life span. Long‐term intervention can improve the physical abilities of individuals with RTT. Low‐, medium‐, and high‐technology interventions can improve the communicative abilities of individuals with RTT. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Revisión de Intervenciones de rehabilitación en el síndrome de Rett: Objetivo: Resumir las intervenciones actuales y sus resultados en la rehabilitación del síndrome de Rett (RTT) e identificar brechas en la literatura. Métodos: Se realizó una búsqueda sistemática de estudios que describieran intervenciones de rehabilitación en cinco bases de datos (Ovid MEDLINE, Ovid Embase Classic, Ovid PsycINFO, EBSCO CINAHL Plus y ProQuest ERIC) hasta el 23 de julio de 2018. Se extrajeron los datos sobre los participantes del estudio, el diseño y los resultados. Resultados: Sesenta y dos artículos fueron incluidos en la revisión final. La evidencia demostró que, con rehabilitación, las mujeres con RTT pueden mejorar sus habilidades motoras gruesas, motoras finas y comunicativas. Las 11 intervenciones dirigidas a mejorar la función motora gruesa, particularmente la deambulación, lograron mejoras funcionales. Veinte de 24 artículos que describen estudios de rehabilitación de la función motora fina lograron disminuir las estereotipias, mejorar el uso funcional de las manos y / o reducir las conductas autoagresivas. Veintiuno de 22 estudios que describen intervenciones de comunicación lograron una mejoría en la toma de decisiones, la comunicación o conductas de socialización. Otros hallazgos claves incluyen la interacción positiva entre los resultados de rehabilitación física y la comunicación, y que las mujeres con RTT pueden mejorar sus habilidades cognitivas durante la intervención. Interpretación: La rehabilitación puede mejorar la vida cotidiana de las mujeres con RTT y sus cuidadores de manera clínicamente significativa. Intervenções de reabilitação em síndrome de Rett: uma revisão de escopo: Objetivo: Sintetizar intervenções existentes e seus resultados na reabilitação da síndrome de Rett, e identificar lacunas na literatura. Método: Cinco bases de dados (Ovid MEDLINE, Ovid Embase Classic, Ovid PsycINFO, EBSCO CINAHL Plus, e ProQuest ERIC) foram revisadas sistematicamente até 23 de julho de 2018 quanto a estudos descrevendo intervenções de reabilitação. Dados sobre participantes dos estudos, desenho e resultados foram extraídos. Resultados: Sessenta e dois artigos foram incluídos na revisão final. A evidência mostrou consistentemente que mulheres com RTT podem melhorar suas habilidades motoras grossas, finas e de comunicação com a reabilitação. Todas as 11 intervenções com foco na função motora grossa, ou seja, deambulação, mostraram melhoras funcionais. Vinte dos 24 artigos descrevendo reabilitação da função motora fina foram bem sucedidos em diminuir estereotipias, melhorando o uso funcional da mão, e/ou reduzindo comportamentos de auto‐lesão. Vinte e um dos 22 estudos descrevendo intervenções para comunicação foram bem sucedidos em treinar tomadas de decisões, linguagem comunicativa, ou comportamento de socialização. Outros achados chave incluem a relação positiva entre resultados físicos e de comunicação, e a capacidade das mulheres com RTT em melhorar suas capacidades cognitivas durante a intervenção. Interpretação: A reabilitação pode impactar a vida diária de mulheres com RTT e seus cuidadores, de formas clinicamente significativas.